KLK6/PAR1 Axis Promotes Tumor Growth and Metastasis by Regulating Cross-Talk between Tumor Cells and Macrophages - Yo Sep Hwang; Hee Jun Cho; Eun Sun Park; Jeewon Lim; Hyang Ran Yoon; Jong-Tae Kim; Suk Ran Yoon; Haiyoung Jung; Yong-Kyung Choe; Yong-Hoon Kim; Chul-Ho Lee; Yong Tae Kwon; et al. (Cells, 2022)
Kallikrein-related peptidase (KLK)6 is associated with inflammatory diseases and neoplastic progression. KLK6 is aberrantly expressed in several solid tumors and regulates cancer development, metastatic progression, and drug resistance. However, the function of KLK6 in the tumor microenvironment remains unclear. This study aimed to determine the role of KLK6 in the tumor microenvironment. Here, we uncovered the mechanism underlying KLK6-mediated cross-talk between cancer cells and macrophages. Compared with wild-type mice, KLK6−/− mice showed less tumor growth and metastasis in the B16F10 melanoma and Lewis lung carcinoma (LLC) xenograft model. Mechanistically, KLK6 promoted the secretion of tumor necrosis factor-alpha (TNF-α) from macrophages via the activation of protease-activated receptor-1 (PAR1) in an autocrine manner. TNF-α secreted from macrophages induced the release of the C-X-C motif chemokine ligand 1 (CXCL1) from melanoma and lung carcinoma cells in a paracrine manner. The introduction of recombinant KLK6 protein in KLK6−/− mice rescued the production of TNF-α and CXCL1, tumor growth, and metastasis. Inhibition of PAR1 activity suppressed these malignant phenotypes rescued by rKLK6 in vitro and in vivo. Our findings suggest that KLK6 functions as an important molecular link between macrophages and cancer cells during malignant progression, thereby providing opportunities for therapeutic intervention.